TINJAUAN KINERJA PELAYANAN ANGKUTAN UMUM PT SINARMAR TANSPORTASI MANDIRI RUTE BUKITTINGGI – PAYAKUMBUH - Jeli Indriani; Ishak Ishak; Selpa Dewi (Ensiklopedia Research and Community Service Review, 2023)
Abstract: This study aims to determine the performance of public transportation services and evaluate the performance of public transportation services on the Bukittinggi – Payakumbuh route. The method used by the researcher uses a Likert and Guttman scale. By distributing a questionnaire of 160 respondents. This research was conducted by means of a survey through the distribution of respondents' questionnaires. After that, the validity and reliability of the questionnaire were tested, then continued with data analysis of the research results. From the results of data analysis, it was obtained that taking the reliability test using 30 respondents to test reliability, the results of the Alpha coefficient of 0.723 were said to be reliable because the Alpha coefficient was above 0.600. The performance of public transportation services at PT Sinarmar Transport Mandiri for the Bukittinggi – Payakumbuh route is quite good, because in the search for high correlation validity results, the highest validity value is 0.966, and the validity results can also be seen from r_(count<r table) so that the data in the calculation is said to be valid.Keywords : Intercity Transportation Within Province, SPSS 25